Use of 177Lutetium-PSMA in the Treatment of Metastatic Castrate-Resistant Prostate Cancer: A Case Report - Nerli, R B; Ghagane, Shridhar C; Bokare, Ashwin; Shetty, Rakesh; Ramesh, Sudha; Rai, Shreyas (Indonesian Journal of Cancer, 2025)
Introduction: Despite several recent advances and the introduction of newer anti-cancer agents, metastatic castrate-resistant prostate cancer (mCRPC) remains challenging to treat and remains fatal. Recent studies have raised the possibility of targeted radionuclide therapies such as 177Lutetium-PSMA (prostate-specific membrane antigen) as a viable therapeutic option in men with metastatic prostate cancer. Case Presentation: A 53-year-old male presenting with lower urinary tract symptoms was found to have cancer of the prostate on further evaluation. The patient underwent radical prostatectomy, and during follow-up, bony metastasis was noted at the end of two years. The patient received androgen deprivation therapy and, over the next ten years, underwent chemotherapy, enzalutamide therapy, and secondary chemotherapy. The patient continued to have painful bony metastasis and was treated with 177Lutetium-PSMA therapy. Conclusion: 177Lutetium-PSMA demonstrates a promising treatment response in men with metastatic castration-resistant prostate cancer (mCRPC).